(untitled) (The Journal of Plant Protection Sciences, 2021)
Biological control of plant diseases seems to be the best alternative for plant disease control. It is ecofriendly, reliable, cost effective and is an integral component of integrated plant disease management framework for sustainable crop production. A considerable number of biocontrol agents have been established successfully for their bioconrol potential including strains belonging to bacterial genera such as Agrobacterium, Pseudomonas, Streptomyces and Bacillus, and fungal genera such as Gliocladium, Trichoderma, Ampelomyces, Candida and Coniothyrium. Trichoderma and Pseudomonas fluorescens are the most important and widely used bioconrol agents being used across the world for the management of several plant diseases. Some bacterial biocontrol agents can inhibit both bacterial and fungal pathogens. Smilarly, fungal-fungal, fungal-bacteria and actinomycete-fungal/actinomycete interactions exist in nature and opens a new area of research in biocontrol of plant diseases. The mechanisms of action of these biocontrol agents against target pathogens are antibiosis, mycoparasitism, competition for space and nutrient, production of certain toxins and secondary metabolites, solublization and sequestration of immobilized plant nutrients, plant growth prowth promoting properties and induced resistance. Multiple interactions between bacteria-fungi-actinomycete, may exist in nature and that is why consortium of microorganisms is needed for tackling several plant pathogens simultaneously instead of only one biocontrol agent-one pathogen,which is the most common and established system of biocontrol of plant diseases.